Canine Renal Nephroblastoma with Multiple Organ Metastasis – A Case Report - Chaitanya , S; Sharma, Sukirti; Sonkusale, P M (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Nephroblastoma or Wilm’s tumor is a rare neoplasm originating from metanephric blastema, stromal cells and blastema. Nephroblastoma may be benign but usually malignant in nature especially in pediatric dogs. Usually, blastema differentiates into nephron unit and the cells which don’t differentiate undergoes apoptosis. A dog from Police Department was brought for a detailed post mortem examination with a history of anorexia, depression, weight loss and recumbency. On physical examination the dog was cachectic and dehydrated and presence of decubitus ulcers. Gross lesions consisted of large tumorous growth in both right kidney and left kidney with multifocal small tumour nodules. Also tumour growth was found attached to the apical lobe of right lung and small tumour nodules on the parenchyma of entire lung Microscopically, blastema cells had high N:C ratio, hyperchromic and mitotic figures. Blastemal cells were seen in other vital organs such as lungs, liver and spleen indicating metastasis.